Day and Night: Metabolic Profiles and Evolutionary Relationships of Six Axenic Non-Marine Cyanobacteria. (24th December 2018) - Will, Sabine Eva; Henke, Petra; Boedeker, Christian; Huang, Sixing; Brinkmann, Henner; Rohde, Manfred; Jarek, Michael; Friedl, Thomas; Seufert, Steph; Schumacher, Martin; Overmann, Jörg; Neumann-Schaal, Meina; et al.
Abstract: Cyanobacteria are dominant primary producers of various ecosystems and they colonize marine as well as freshwater and terrestrial habitats. On the basis of their oxygenic photosynthesis they are known to synthesize a high number of secondary metabolites, which makes them promising for biotechnological applications. State-of-the-art sequencing and analytical techniques and the availability of several axenic strains offer new opportunities for the understanding of the hidden metabolic potential of cyanobacteria beyond those of single model organisms. Here, we report comprehensive genomic and metabolic analyses of five non-marine cyanobacteria, that is, Nostoc sp. DSM 107007, Anabaena variabilis DSM 107003, Calothrix desertica DSM 106972, Chroococcidiopsis cubana DSM 107010, Chlorogloeopsis sp. PCC 6912, and the reference strain Synechocystis sp. PCC 6803. Five strains that are prevalently belonging to the order Nostocales represent the phylogenetic depth of clade B1, a morphologically highly diverse sister lineage of clade B2 that includes strain PCC 6803. Genome sequencing, light and scanning electron microscopy revealed the characteristics and axenicity of the analyzed strains. Phylogenetic comparisons showed the limits of the 16S rRNA gene for the classification of cyanobacteria, but documented the applicability of a multilocus sequence alignment analysis based on 43 conserved protein markers. The analysis of metabolites of the core carbon metabolism showed parts of highly conserved metabolic pathways as well as lineage specific pathways such as the glyoxylate shunt, which was acquired by cyanobacteria at least twice via horizontal gene transfer. Major metabolic changes were observed when we compared alterations between day and night samples. Furthermore, our results showed metabolic potential of cyanobacteria beyond Synechocystis sp. PCC 6803 as model organism and may encourage the cyanobacterial community to broaden their research to related organisms with higher metabolic activity in the desired pathways.